2004
DOI: 10.1111/j.1365-2249.2004.02657.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies cross-reacting with thyroglobulin and thyroid peroxidase are induced by immunization of rabbits with an immunogenic thyroglobulin 20mer peptide

Abstract: SUMMARYThyroglobulin (Tg) and thyroid peroxidase (TPO) are two major autoantigens in autoimmune thyroid diseases (AITD). Cross-reactive anti-Tg/TPO antibodies have been identified in patients with AITD and in mice immunized with Tg or TPO. In the present study, we investigated the production of anti-Tg/ TPO antibodies in rabbits immunized with human Tg and with a highly immunogenic Tg peptide (namely TgP41, sequence 2651-2670 of human Tg), by noncompetitive and competitive ELISA. TgP41 was found previously to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Induced and spontaneous intermolecular spreading for thyroid autoantibodies has been demonstrated for thyroid autoimmunity (Table 2 ). For example, rabbits immunized with human Tg and complete Freund’s adjuvant develop antibodies to Tg, as expected, as well as antibodies to TPO and antibodies that bind to both Tg and TPO ( 85 , 86 ). It should be noted that searching for previously postulated bispecific human autoantibodies that recognize both Tg and TPO (“TgPO antibodies”) [for example, Ref.…”
Section: Epitope Spreading Of Thyroid Autoantibodiessupporting
confidence: 53%
“…Induced and spontaneous intermolecular spreading for thyroid autoantibodies has been demonstrated for thyroid autoimmunity (Table 2 ). For example, rabbits immunized with human Tg and complete Freund’s adjuvant develop antibodies to Tg, as expected, as well as antibodies to TPO and antibodies that bind to both Tg and TPO ( 85 , 86 ). It should be noted that searching for previously postulated bispecific human autoantibodies that recognize both Tg and TPO (“TgPO antibodies”) [for example, Ref.…”
Section: Epitope Spreading Of Thyroid Autoantibodiessupporting
confidence: 53%
“…The reason for this epitope masking is currently not clear, but it is intriguing to speculate that this phenomenon might reduce the potential immunogenicity of some of the therapeutic Abs when comprised in a pAb composition. Also, these studies demonstrated the absence of epitope spreading (18,19). Hence, Abs which are nonimmunogenic when administered individually did not become immunogenic as part of a pAb composition.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, we identified spreading of B cell epitopes within the molecule of Tg (intramolecular spreading) after active immunization with a 20mer Tg peptide [5]. This intramolecular spreading in Tg resulted in intermolecular spreading of antibody reactivity to another thyroid antigen, thyroid peroxidase (TPO) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Immunization of rabbits with Tg is known to result in the generation of antibodies to the thyroid antigen TPO [6]. In the present study we investigated spreading of antibody reactivity to non‐thyroid autoantigens during immunization of rabbits with human Tg.…”
Section: Introductionmentioning
confidence: 99%